Pemodelan Perhitungan Cadangan Batubara Dengan Perangkat Lunak Pada PT. Mitra Abadi Mahakam Provinsi Kalimantan Selatan - Avellyn Shinthya Sari; Minto Basuki; Satria Ambara Iriawan (Fakultas Teknologi Informasi Institut Teknologi Adhi Tama Surabaya, 2017)
This company needs reserves calculation before doing mining activities such as coal deposit model construction, coal reserves calculation. and Stripping Ratio (SR) value calculation. As a result, it obtains the number of coal reserves which will coal deposit model. This fact became the background of the study. The reserves calculation was carried out by Triangular Method supported by Minescape software. The coal reserves calculation and coal deposit model of Mitra Abadi Mahakam Ltd.. The research result was a coal model which can be seen from the pictures on map attached in this final project report. The coal reserve was 2,347,827.44 tons, while the overburden volume of mining activity site was 8,318,130.05 BCM